Викривач як суб'єкт протидії корупційним та іншим порушенням законодавства - Косиця, О. О.; Kosytsia, O. O.; ORCID: http://orcid.org/0000-0002-5781-780X; ResearcherID: C-6889-2018 (Юридичний науковий електронний журнал. - 2019. - № 1. - C. 133-137, 2019)
Статтю присвячено аналізу поглядів вітчизняних та зарубіжних науковців на поняття «викривач». Проаналізовано таку ознаку викривання як добросовісність. Запропоновано вважати, що викривач протидіє не лише корупційним, але й іншим порушенням законодавства і в усіх випадках потребує захисту держави. Наведено приклади та основні тези з рішень Європейського суду з прав людини щодо застосування статті 10 Конвенції про захист прав людини і основоположних свобод 1950 року, пов’язаних зі свободою вираження поглядів та подальшими негативними наслідками, які можна називати справами із захисту викривачів.

The article is devoted to the analysis of the views of domestic and foreign scholars on the concept of " whistle-blower". The analysis and generalization of the norms of the Law of Ukraine "On Prevention of Corruption" indicates that the discloser is: 1) a person who reports in good faith on possible facts of corruption or corruption-related offenses, and other violations of the Law of Ukraine "On Prevention of Corruption"; 2) an assistant in the prevention and counteraction of corruption; 3) a person who, in the presence of a reasonable belief that the information is reliable, reports a violation of the requirements of the Law of Ukraine "On Prevention of Corruption" by another person. Based on the analysis of approaches to such a feature of disclosure as integrity, we believe that the principle of conscientiousness in exposing corruption and other violations of the law is as follows: fulfillment of the moral obligation of the individual towards other persons and society; absence of any deception; lack of intent to cause harm to another person; understanding responsibility for their actions. It is advisable to consider introducing a mandatory requirement to whistleblowering as voluntary. The most famous cases of the European Court of Human Rights regarding the protection of the rights of deniers, namely the application of Article 10 of the 1950 Convention for the Protection of Human Rights and Fundamental Freedoms (right to freedom of expression) are given. It has been established that there are a number of cases related to the freedom of expression of views of both non-state and civil servants, and the state has a positive obligation to protect the right to freedom of expression, even in the field of relations between private individuals. It is suggested to assume that counteraction to corruption is not the only sphere of public life in which the law is violated and in which the rights of those persons who during the course of their labour (economic, public, official, etc.) activity have found out violations and voluntarily informed about them.

Статья посвящена анализу взглядов отечественных и зарубежных ученых на понятие «обличитель». Проанализирован такой признак обличения как добросовестность. Предложено считать, что обличитель противодействует не только коррупционным, но и другим нарушением законодательства и во всех случаях нуждается в защите государства. Приведены примеры и основные положения из решений Европейского суда по правам человека по применению статьи 10 Конвенции о защите прав человека и основных свобод 1950 года, связанных со свободой выражения и последующими негативными последствиями, которые можно называть делами по защите обличителей.
«Whistle-blower» as a subject of counteraction anti-corruption and other law violations
Обличитель как субъект противодействия коррупционным и иным нарушением законодательства
Косиця О. О. Викривач як суб’єкт протидії корупційним та іншим порушенням законодавства [Електронний ресурс] / Косиця О. О. // Юридичний науковий електронний журнал. - 2019. - № 1. - C. 133-137. - Режим доступу: http://www.lsej.org.ua/1_2019/36.pdf.
Keywords: викривач; обличитель; whistle-blower; викривання; державний захист прав викривачів; рішення Європейського суду з прав людини; принцип добросовісності; Конвенція про захист прав людини і основоположних свобод; обличение; государственная защита прав обличителей; решение Европейского суда по правам человека; Конвенция о защите прав человека и основных свобод; принцип добросовестности; whistleblowering; state defense of the rights of the disclosers; decision of the European Court of Human Rights; Convention on the Protection of Human Rights and Fundamental Freedoms; principle of good faith; Міжнародне право .International Law. Международное право; Наукові публікації. Scientific publications. Научные публикации